Biblical gender equality and women's participation in leadership - Nwoko, Michael N; Igbokwe, Clement Chimezie (Postgraduate Program of State Islamic University (UIN) Salatiga Jl. Lingkar Salatiga Km. 02 Salatiga, Indonesia https://pps.uinsalatiga.ac.id/, 2023)
Lack of women participation in leadership positions has remained central in efforts to create an all-inclusive men-women sensitive society. Biblically, there is a resilient indication of God’s intention for women’s involvement in leadership positions. This study discusses biblical evidence supporting women's full participation in leadership and decision-making activities. The theoretical review was anchored on the tripartite approach of transformation theory of leadership, patriarchy, and liberal feminism. Methodologically, the study relied solely on secondary data collection, applying content and documentary analysis. The findings of the study showed that there are female Bible characters who demonstrated faith and exerted influence on society, successfully fulfilling their roles according to Biblical teaching. Further findings indicated that even in the ministry of Jesus Christ, women played significant roles and contributed to fulfilling his earthly mission. One of the study's recommendations was to implement affirmative action (also known as positive discrimination) as a strategy to overcome structural obstructions in male-biased institutions. This should be adopted by political parties, economic, religious, and social institutions, as well as bureaucracies.